The Effectiveness of Computer Games Rehabilitation and Cognitive Play Therapy Rehabilitation on the Risk-Taking of Children with Attention Deficit Hyperactivity Disorder - Nazerieh, ٍElaheh; Niknam, Mandana (International Journal of Applied Behavioral Sciences, 2024)
Background and Aim: Attention Deficit Hyperactivity Disorder(ADHD) is one of the most prevalent disorders of childhood with several consequences. This study aimed to compare the effectiveness of cognitive computer games rehabilitation and play therapy based on cognitive rehabilitation on the risk-taking of children with attention deficit hyperactivity disorder. Method and material: the research method was semi-experimental with a pre-test-post-test design, a waiting list, and a one-month follow-up study. The statistical population included all children aged 7 to 12 years old with attention-deficit/hyperactivity disorder in Karaj city, 24 children referred to the Razi counseling center in 2020-2021 were selected by available sampling method and were randomly replaced in groups: cognitive computer games (8 children), cognitive play therapy (8 children) and control (8 children). The experimental groups received related interventions and the waiting list did not receive any treatment during this time. The balloon analog risk task (BIS) was used to collect data. Data analysis was done using analysis of variance with repeated measures and Bonferroni's post hoc test. Results: The findings showed that cognitive computer games and play therapy based on cognitive rehabilitation are effective in the risk-taking of children with attention deficit hyperactivity disorder (P<0.05). Also, the findings showed a significant difference between the effectiveness of the two interventions in risk-taking Conclusion: play therapy based on cognitive rehabilitation was more effective than cognitive computer games in reducing risk-taking.cognitive computer games; Play therapy; Cognitive rehabilitation; Risk-taking; Attention deficit hyperactivity disorder